Managing power the role of power in the community-oriented policing system as exercised at the Iloilo City police office - Caton, Ulysses C. (University of the Philippines Visayas, 2004)
It has been struggle for the Philippine National Police to prevent and suppress crimes in an organized society. To address these problems, various programs have been created, the COPS Program being one of these. COPS was designed to involve not only the police force but the other sectors of society as well. While participation is the guiding principle of this program, critical to its success is the middle-level police managers' exercise of leadership. The study, however, recognizes the broad scope of leadership as an area for research. Thus, the focus of this study will be on one of the critical and vital ingredient of leadership, which is power. The study focused on the role of power as exercised by police managers in the implementation of the COPS program. Several problems are being addressed to determine the extent to which police managers posses various types of power, the differences in perception in the exercise of power between plice managers and subordnates nd the power-related issues and problems that may affect the implementation of the COPS program/ The study employed the descriptive research design. Questionnaires were administered to generate primary data and draw secondary from various published management articles and documents. All COPS program implementers were selected purposely as respondents of the study. The data was the analyzed using descriptive statistics. The result of survey regarding perception as to the extent to which police managers possess various types of power revealed that while all respondents agree that police mangers exercise competence in the issuance of orders, control operations, imposition of sanctions, and distribution of rewards, the two groups (police manager and PNP subordinates) disagree in terms of quality. Police managers on the average, responded that they are "very competent" while subordinates felt that their police managers are just "competent". Likewise, the willingness of police managers to provide official recognition for exemplary performance or impose disciplinary sanctions for violation of PNP rules and regulations of subordinates, police managers responded that they are "very willing" while the subordinates perceive that they are just somewhat "willing". Majority of the respondents have specified [power related problem and issues that nay affect the implementation of the COPS program and suggested various recommendations. The researcher also recommends that police managers should exercise an approapriate type of power and according to the prescribed rules and regulations and should not be influenced by other individuals with self-interests. Also, PNP subordinates shoul develop the necessary competence in the performance of their assigned tasks. All these recommendations can improve the COPS program implementation.